Introducing an E-learning Solution for Medical Education in Liberia - S. Walsh; M. R. de Villiers; V. K. Golakai (Ubiquity Press, 2018)
Background: The Ebola virus epidemic and civil war in Liberia left the country in need of strengthening the health workforce. E-learning in medical education provides relevant learning opportunities for students, develops faculty competencies, and assists with the retention of healthcare workers. The Stellenbosch University Rural Medical Education Partnership Initiative (SURMEPI), the College of Health and Life Sciences (COHLS) at the University of Liberia (UL), and the Health Resources and Services Administration (HRSA) formed a partnership to create an e-learning solution for the COHLS. Objective: This article outlines the implementation of an e-learning solution for the COHLS in Monrovia, and describes the challenges met, the key successes achieved, and the lessons learnt. Methods: An initial scoping visit to Liberia was followed by three further on-site visits. Problems identified were: very limited or no network and computer resources, no internet connection, intermittent power, and lack of IT skills. We followed an evolutionary approach to infrastructure implementation by trying various solutions before settling on an offsite-hosted solution using Software as a Service (SaaS). Local staff were upskilled to administer this while remote support from Stellenbosch IT was provided. A stable internet connection was established. Staff and students can access the Learning Management System (LMS) 24/7 using mobile devices and laptops. Workshops were held where staff were taught how to produce online teaching material. Each class has at least one teaching assistant to assist lecturers with uploading and indexing material on the LMS. A benchmarking visit by COHLS faculty to Stellenbosch University took place, during which an e-learning strategic plan was drawn up. Further online workshops were conducted, and teaching materials were placed on the new LMS. Outcomes: The intranet that was established consisted of internet connection and software as a service in the form of Office 365, providing access to several products and services. The e-learning model attended to technology and human resources simultaneously. The e-learning strategy aimed to improve teaching and learning at the COHLS, boost the number of qualified doctors, reduce the workload on lecturers, and be scalable in the future. Conclusion: It is challenging to implement e-learning in medical education. Inadequate infrastructure, limited bandwidth, lack of skilled IT staff, unreliable power supply, time commitment, and ongoing maintenance all need to be overcome. The creation of an e-learning solution for the COHLS over a period of 15 months was enabled by the common vision and close collaboration of the three partners. This model can potentially be replicated across other faculties in the University of Liberia and other educational institutions in Liberia.